2019
DOI: 10.1186/s13045-019-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing for BCR-ABL1 kinase domain mutation testing in patients with chronic myeloid leukemia: a position paper

Abstract: BCR-ABL1 kinase domain (KD) mutation status is considered to be an important element of clinical decision algorithms for chronic myeloid leukemia (CML) patients who do not achieve an optimal response to tyrosine kinase inhibitors (TKIs). Conventional Sanger sequencing is the method currently recommended to test BCR-ABL1 KD mutations. However, Sanger sequencing has limited sensitivity and cannot always discriminate between polyclonal and compound mutations. The use of next-generation sequencing (NGS) is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 72 publications
1
53
0
1
Order By: Relevance
“…Next generation sequencing (NGS) allows for the detection of low-level BCR-ABL1 kinase domain mutations as well as resistance mutations in genes other than BCR-ABL1 that may confer resistance to TKIs or portend disease progression. [62][63][64][65] In a recent prospective, multicenter study (NEXT-in-CML) that assessed the feasibility of NGS in detection of low-level mutations in 236 consecutive patients with CML and inadequate response to TKI therapy, NGS was more effective than conventional Sanger sequencing in the detection of low-level mutations. 65 Prospective monitoring of mutation kinetics demonstrated that TKI-resistant low-level mutations are invariably selected if the patients are not switched to another TKI or if they are switched to an inappropriate TKI or TKI dose.…”
Section: Role Of Next Generation Sequencingmentioning
confidence: 99%
“…Next generation sequencing (NGS) allows for the detection of low-level BCR-ABL1 kinase domain mutations as well as resistance mutations in genes other than BCR-ABL1 that may confer resistance to TKIs or portend disease progression. [62][63][64][65] In a recent prospective, multicenter study (NEXT-in-CML) that assessed the feasibility of NGS in detection of low-level mutations in 236 consecutive patients with CML and inadequate response to TKI therapy, NGS was more effective than conventional Sanger sequencing in the detection of low-level mutations. 65 Prospective monitoring of mutation kinetics demonstrated that TKI-resistant low-level mutations are invariably selected if the patients are not switched to another TKI or if they are switched to an inappropriate TKI or TKI dose.…”
Section: Role Of Next Generation Sequencingmentioning
confidence: 99%
“…Such patients may have acquired point mutations in the kinase domain (KD) of BCR-ABL1 that impair TKI binding. Detailed lists of mutations conferring resistance to each TKI are currently available [5]. Although other mechanisms of resistance have been reported, BCR-ABL1 KD mutations are, at present, the only "actionable" one, since the detection of a TKI-resistant mutation mandates a change of therapy and the type of mutation may guide the selection of the second-or subsequent-line TKI [6].…”
Section: Introductionmentioning
confidence: 99%
“…Computational analysis tools for RNA sequencing have dramatically increased during the past decade. The choice of a particular tool should be based on the purpose and accuracy of application [29][30][31]. A general RNA sequencing data analysis process involves the quality control of raw data, read alignment and transcript assembly, expression quantification and differential expression analysis (Fig.…”
Section: Computational Analysis Of Rna Sequencing Datamentioning
confidence: 99%